Implementasi Komunikasi Lingkungan Pada Kepemimpinan Parabela dalam Menjaga Kelestarian Lingkungan Berbasis Kearifan Lokal di Kabupaten Buton - Husain, M. Najib; Haryadi, F. Trisakti; Wastutiningsih, Sri Peni (2012)
There are three purpose of the study. First it is intended do know the roles of parabela leadership in maintaining Kaombo area . Second , the study describes the governance of environmental communication in parabela leadership in maintaining Kaombo area. At last the study is aimed at identifying the impact of interpersonal communication in Parabela leadership on the changes of community attitudes in Kaombo area. in this case , the setting of the study is focused on the period after the regional autonomy policy . Moreover , the study employes ethnografy appoach. Besides, this study is donne in Kabupaten Buton by enggaging informants-Parabela and its personel, the head of village, community leaders , and community , The results of the research using ethnograpic aproach show that Parabela implement result of the research using ethnograpic approach show that Parasbela implement both of the fuction , but the first fuction- progmatic- is more succesfull.